The Resource Pool System on a Rice Farm Based on Pumping Irrigation in Tempe Lake, Indonesia - A. Majdah M.Zain, Rahim Darma, Awaluddin Yunus, And. Kasirang T. Baso, A.Tenri Darhyati, Rida Akzar (International Journal of Control and Automation, 2020)
The resource pool is a model that helps to meet water needs in rice farming. Each production factor has benefits and risks based on the value of resources. The research objective is to value the production factors used on a rice farm. The research method used to achieve this includes a case study on a group of rice farmers around the edge of the lake. Financial analysis is also used as the basis for valuing the resources incorporated into rice farming. Farmers, as owners of labor, capital, and skills, have a higher benefit and risk, followed by landowners and providers of irrigation services. Risks faced by landowners include the opportunity cost of land, rent, and high land values. The risk of irrigation service providers is the total operational costs and the depreciation of equipment, which is equivalent to land rent. Break-Even Point (BEP) productivity is inversely proportional to business risks and benefits. BEP of productivity is 1.8 for farmers, 2.37 for landowners, and 2.27 for irrigation service providers. The share of water resources can be used as a reference to water fees on conventional irrigation.